Faktor Pengetahuan, Sikap, Dan Praktik Dalam Pemberian Asi Ekslusif Pada Anak - Tri Dela Puspita; Marina Valentia Putri Lubis; Widia Lestari; Rani Suraya (CV. ITTC INDONESIA, 2025)
Exclusive breastfeeding for the first six months of a baby's life still faces various challenges, particularly related to mothers' knowledge, attitudes, and practices. This study aims to analyze the factors influencing the success of exclusive breastfeeding in Jatirejo Village, Pagar Merbau District. The research method used is descriptive quantitative with a questionnaire survey involving 30 mothers with children aged 0–24 months. The results show that most mothers have a good understanding of exclusive breastfeeding. However, several challenges remain, such as perceptions of low breast milk production, work demands, and lack of education. On the other hand, support from family and healthcare professionals plays a crucial role in the success of exclusive breastfeeding. Therefore, continuous education and policies supporting breastfeeding mothers, especially working mothers, are necessary.